Fowler’s syndrome—Patient led phenotyping of 265 patients - Emily R. Cox; J.N. Panicker; D. Coombe; C. Selai; D. Ellis; J. Stone; I. Hoeritzauer (Continence)
Aims:: To better understand Fowler’s syndrome from a patient perspective. Methods:: The survey was created by the Fowler’s syndrome UK charity(FSUK, registered charity number 1196903), and advertised to patients with a diagnosis of Fowler’s syndrome via social media from December 2021 to March 2022. Results:: Of 265 participants, 187 (70%) were aged between 15–30 years. Patients self-reported Fowler’s syndrome. Medical notes were not obtained. However, 195 (74%) were diagnosed by either urethral sphincter EMG or urethral pressure profile suggesting a representative sample, with few differences in those not reporting those investigations. 183 (69%) experienced complete urinary retention. Over 75% reported pain in either their bladder, urethra or pelvis. 224 (84%) used catheters to manage symptoms and 80% were taking opiates for pain. Sacral neuromodulation was offered to 75% of patients and found useful by 27% of these patients. Urethral sphincter or detrusor botulinum toxin, pain management, or physiotherapy were offered to between 32%–61% of patients and found beneficial in less than a third of those undertaking them. Over 50% rated impact on life overall as ‘severe’. Over 80% required help with ADLs on their worst day. 200 (75%) reported being told that their symptoms were due to anxiety, “imaginary” or “all in their head”. Conclusions:: This is the largest cross-sectional study of women with Fowler’s syndrome. Fowler’s syndrome severely affected quality of life in >50%. Current management options available were recorded as beneficial in fewer than a third of participants. The majority of participants felt unsupported by medical professionals.